PELATIHAN KEMAMPUAN MEMBACA HURUF HIJAIYAH DENGAN BANTUA MEDIA PAPAN KARTU ARABIYAH PADA MASYARAKAT RW04 LINGKUNGAN CANGKRING PATRANG - Ahmad Halid (’Ibadatuna : Jurnal Pengabdian Masyarakat, 2024)
This training inspires every Muslim to be able to read the Koran and practice it. The objects of this training are the ladies and gentlemen of RW 04 of the Cangkring Patrang Jember neighborhood. The objectives of this training are (1) to teach people to recognize hijaiyah letters, (2) to be able to read the Koran properly and correctly (3) to be able to use the Koran as a guide for their lives in all matters and circumstances. , (4) enjoy and love the Koran by routinely reading it and applying the contents of the verses of the Koran. This training was carried out in three stages, namely planning, implementing and evaluating the training. The results of the training are that the community has succeeded in (1) recognizing (understanding) the hijaiyah letters, (2) being able to read the Qur’an well and correctly (3) being able to use the Qur’an as a guide for their lives in all matters and their condition, (4) happy and loving the Koran by routinely reading it and applying the contents of the verses of the Koran.